Community pharmacists' knowledge and experience regarding malaria management: a cross-sectional study in Hodeida, Yemen - Halboup, Abdulsalam M.; Harun, Sabariah Noor; Ghadzi, Siti Maisharah Sheikh; Sulaiman, Syed Azhar Syed; Ibrahim, Doaa Anwar; Areqi, Abdullah Ahmed; Al-Ashwal, Fahmi Y. (BioMed Central (BMC), Springer Nature, 2025)
Background:Malaria remains a significant public health concern in Yemen, ranking fourth in incidence within the Eastern Mediterranean Region. Community pharmacists play a pivotal role in malaria management and often dispense anti-malarial medications without prescriptions. However, little is known about their knowledge and adherence to the National Policy for Antimalarial Drugs. This study aimed to evaluate pharmacists' knowledge, experience, and perceived barriers regarding malaria management in Hodeidah, Yemen.Methods:A cross-sectional study was conducted between May and August 2023 across 320 community pharmacies in 16 districts of Hodeidah governorate. A validated questionnaire was used to assess pharmacists' knowledge, experience, and perceived barriers to effective malaria management. Descriptive statistics and logistic regression analysed the associations between sociodemographic factors and pharmacists' knowledge and experience.Results:Of the 304 respondents, 10 were excluded due to incomplete data, yielding a valid response rate of 91.9% (294). Most pharmacies were independent (74.8%), and 51.4% were located in Hodeidah city. The majority of the pharmacists were male (92.2%), aged 1930 years (50.3%), and held a pharmacy diploma (69%). Poor knowledge of malaria management was observed in 76.5% of respondents (mean: 9.96, SD 3.47), with only 34.4% and 43.2% accurately identifying first-line treatments for uncomplicated and complicated malaria, respectively. Additionally, 60.9% were aware of the prevalent malaria species, and 53.1% knew the correct diagnostic methods. However, only 17.0% recognized high-risk groups for complicated malaria, 18.4% identified causes of treatment failure, and 7.8% understood the consequences of malaria during pregnancy. In terms of experience, 76.2% of the participants reported inadequate experience related to anti-malarial medications (mean: 56.71, SD 7.32), with the main barriers being lack of training (78.9%) and insufficient knowledge (73.5%). Multivariable logistic regression revealed that older age (AOR: 6.827, p = 0.020), holding a pharmacy diploma (AOR: 2.555, p = 0.036), and fewer perceived barriers (AOR = 3.830, p < 0.001) were predictors of poor knowledge, whereas practicing in Hodeidah city (AOR = 1.865, p = 0.043) predicted inadequate experience.Conclusion:Community pharmacists in Hodeidah demonstrate significant gaps in knowledge and experience related to malaria management. Urgent educational interventions are needed to enhance pharmacists' competency, ensure effective malaria treatment, and prevent the emergence of drug resistance in Yemen.